Działalność I sekretarza Komitetu Warszawskiego PZPR Stefana Staszewskiego w 1956 roku - Juzepczuk, Marek (Pamięć i Sprawiedliwość, 2017)
Stefan Staszewski, born in 1906 in Warsaw as Gustaw Szuster, was an active member of the Young Communist League of Poland and the Communist Party of Poland, trained from 1926 to 1928 in the International Lenin School in Moscow. He was arrested three times in Poland for communist activity. In 1934, he fled to the USSR, where he was reprimanded for membership in M. Lampe’s group, and then expelled from the AUCP(b) and arrested by the NKVD. He was sentenced to 15 years in a Kolyma Gulag camp. He was released in 1945 thanks to Bolesław Bierut’s intervention, and after coming to Poland, he joined the Polish Workers’ Party (PPR) and changed his name to Stefan Staszewski. The Secretary of the PPR Central Committee dispatched him to Katowice to take the position of the secretary for industrial affairs. Soon, he became the editor-in-chief of Trybuna Robotnicza, which achieved considerable success under his management. In 1948, the party leadership gave him the very responsible post of the director of the Department of Press and Publications of the PUWP’s Central Committee. Staszewski changed radically the organizational system of the party press and of the publishing businesses’ activity, and contributed to the development of communist journalism. In 1954, he was dismissed from the post of the Department of Press and Publications’ head and moved to the Ministry of Agriculture. During the thaw, he became a critic of the former party leadership and began to actively aid supporters of reforms. As the First Secretary of the PUWP Warsaw Committee, in October 1956 he organized and supervised rallies at Warsaw universities and work places. During the Eighth Plenary Session of the PUWP Central Committee, he was attacked by activists belonging to the “Natolinian group”. His stance was violently criticised by Soviet leader Nikita Khrushchev, which resulted in his dismissal from the post of secretary of the Warsaw party organization. Staszewski largely contributed to the success of the party reformers and to positive transformations initiated during the Eighth Plenary Session. Having left the PUWP Warsaw Committee, he worked for a short time in the Polish Press Agency. His relationship with new party authorities steadily became worse, which resulted in him being removed from the post of the assistant of the member of PUWP Central Committee. That is why he began to work for the State Scientific Publishers (PWN) in the editorial section of the Great Universal Encyclopaedia. In 1968, party propaganda presented him, together with Roman Zambrowski, as the most dangerous threat to the PRL’s constitutional order. In the 1970s, he maintained close relations with the Workers’ Defence Committee. Under martial law, his flat was searched by the Security Service.